The Effect of AI-Supported English Literary Instruction on Learning Archaic Vocabulary among EFL Students - Abdulghani Abouzied; DafaAllah Ibrahim; Khuloud Alouzi; Mowafg Abrahem; Bushra Alfallah; Mohieddin Masoud (Asshika: Journal of English Language Teaching and Learning, 2025)
Learning archaic vocabulary remains a serious challenge for students studying English literature in an English-as-a-Foreign-Language (EFL) context. This study examines the effect of combining English literary texts with artificial intelligence (AI) tools on the learning of archaic vocabulary among undergraduate students at the Faculty of Languages and Translation, University of Zawia, Libya. The study used a quasi-experimental mixed-methods design with 60 EFL students, divided into an experimental group (n = 30) and a control group (n = 30). Both groups completed a pre-test and a post-test to measure their knowledge of archaic vocabulary in literary texts. The experimental group received AI-supported literary instruction, while the control group received conventional vocabulary instruction. The results showed that both groups improved, but the experimental group achieved much higher gains, rising from a pre-test mean of 9.83 to 16.27, while the control group increased from 9.71 to 12.08. An independent-samples t-test showed a significant difference between the two groups, t(58) = 7.65, p < .001. The questionnaire results also showed very positive student perceptions toward the AI-supported approach. The findings indicate that integrating AI tools into literature-based instruction can improve learning of archaic vocabulary and increase student engagement in EFL higher education.